2014
DOI: 10.1007/s11010-014-2024-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of hydrogen-rich water alleviates renal injury in spontaneous hypertensive rats

Abstract: In hypertensive animals and patients, oxidative stress represents the primary risk factor for progression of renal disease. Recently, it has been demonstrated that hydrogen, as a novel antioxidant, can selectively reduce hydroxyl radicals and peroxynitrite anion to exert therapeutic antioxidant activity. Herein, we investigated the protective effect of hydrogen-rich water (HW) against renal injury in spontaneously hypertensive rats (SHR). The 8-week-old male SHR and age-matched Wistar-Kyoto rats were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…We have shown that hydrogen suppresses signaling pathways in allergies [ 26 ] and inflammation [ 27 ] without directly scavenging reactive oxygen/nitrogen species. Signaling molecules that are modulated by hydrogen include Lyn [ 26 , 28 ], Ras [ 29 ], MEK [ 29 , 30 ], ERK [ 12 , 24 , 29 37 ], p38 [ 12 , 16 , 24 , 27 , 30 , 32 , 33 , 35 – 41 ], JNK [ 13 , 24 , 27 , 30 , 32 , 33 , 35 – 38 , 40 , 42 47 ], ASK1 [ 27 , 46 ], Akt [ 12 , 29 , 36 , 37 , 48 , 49 ], GTP-Rac1 [ 36 ], iNOS [ 27 , 34 , 36 , 50 52 ], Nox1 [ 36 ], NF-κB p65 or NF-κB [ 12 , 14 , 27 , 35 – 38 , 40 , 41 , 43 , 49 , 53 75 ], IκBα [ 27 , 40 , 41 , 54 , 60 , 62 , 69 , 73 , 76 ], ST...…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that hydrogen suppresses signaling pathways in allergies [ 26 ] and inflammation [ 27 ] without directly scavenging reactive oxygen/nitrogen species. Signaling molecules that are modulated by hydrogen include Lyn [ 26 , 28 ], Ras [ 29 ], MEK [ 29 , 30 ], ERK [ 12 , 24 , 29 37 ], p38 [ 12 , 16 , 24 , 27 , 30 , 32 , 33 , 35 – 41 ], JNK [ 13 , 24 , 27 , 30 , 32 , 33 , 35 – 38 , 40 , 42 47 ], ASK1 [ 27 , 46 ], Akt [ 12 , 29 , 36 , 37 , 48 , 49 ], GTP-Rac1 [ 36 ], iNOS [ 27 , 34 , 36 , 50 52 ], Nox1 [ 36 ], NF-κB p65 or NF-κB [ 12 , 14 , 27 , 35 – 38 , 40 , 41 , 43 , 49 , 53 75 ], IκBα [ 27 , 40 , 41 , 54 , 60 , 62 , 69 , 73 , 76 ], ST...…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have found that molecular hydrogen has potent pharmacological effects via reducing oxidative stress, inflammation, and apoptosis 5 7 . Molecular hydrogen has emerged in the form of hydrogen-rich water, or inhaled hydrogen gas, and is recommended as an effective treatment for cardiac arrest in clinical applications (HYBRID II TRILA; Ministry of Health, Labour and Welfare of Japan, No.…”
Section: Introductionmentioning
confidence: 99%
“…Protective effects with hydrogen rich water (HW) on kidney have been shown in rats with spontaneous hypertension, 3) metabolic syndrome in SHR.Cg-Leprcp/ NDmcr rat kidney, 4) renal ischemia-reperfusion injury, 5) nephrotoxicity induced by ferric nitrilotriacetate, 6) gentamicin 7) or cisplatin, 8) etc. It has also been documented that HW improve metamorphosis and nephrotoxicity induced by reactive oxygen species (ROS) triggered by cisplatin.…”
mentioning
confidence: 99%